2021
DOI: 10.1590/0100-3984.2020.0010
|View full text |Cite|
|
Sign up to set email alerts
|

Placental magnetic resonance imaging: normal appearance, anatomical variations, and pathological findings

Abstract: Placental magnetic resonance imaging (MRI) has been increasingly requested, especially for the evaluation of suspected cases of placental adhesive disorders, generally known as placenta accreta. Abdominal radiologists need to become familiar with normal placental anatomy, anatomical variations, the current terminology, and major placental diseases that, although rare, are important causes of maternal and fetal morbidity and mortality. The aim of this didactic pictorial essay is to illustrate various findings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The percentage of studies that addressed the use of magnetic resonance imaging for the evaluation of fetal brain alterations was 29.16% and the articles that presented studies specifically on the gestational consequences of Zika Virus infection corresponded to 12.50% of the total number of studies analyzed. Evaluation of the fetal skeleton [4] Ventriculomegaly [15] Changes in the development of the spine and spinal cord [18] COVID-19 [11] Preeclampsia and brain development [9] Abdominal Malformations (1) [12] Abdominal Malformations (2) [21] Oral teratoma [19] Brain Measurements / Uterine Growth Restriction [20] Hydatidiform spring [22] Brain malformations caused by Zika Virus [14] Placental changes [6] 3D Reconstructions Prototypes [23] 22 Microcephaly related to congenital Zika virus infection [24] 23 Changes in the Central Nervous System (microcephaly) related to congenital Zika virus infection [25] It was observed that 8.34% of the articles discussed placental problems, malformations and uterine pathologies, abdominal malformations, head, and neck diseases, in addition to 3D prototyping. Still, 4.16% of the studies studied non-obstetric indications for maternal MRI, hydatidiform mole, fetal skeletal structure, in addition to alterations in the development of the fetal spine and spinal cord (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of studies that addressed the use of magnetic resonance imaging for the evaluation of fetal brain alterations was 29.16% and the articles that presented studies specifically on the gestational consequences of Zika Virus infection corresponded to 12.50% of the total number of studies analyzed. Evaluation of the fetal skeleton [4] Ventriculomegaly [15] Changes in the development of the spine and spinal cord [18] COVID-19 [11] Preeclampsia and brain development [9] Abdominal Malformations (1) [12] Abdominal Malformations (2) [21] Oral teratoma [19] Brain Measurements / Uterine Growth Restriction [20] Hydatidiform spring [22] Brain malformations caused by Zika Virus [14] Placental changes [6] 3D Reconstructions Prototypes [23] 22 Microcephaly related to congenital Zika virus infection [24] 23 Changes in the Central Nervous System (microcephaly) related to congenital Zika virus infection [25] It was observed that 8.34% of the articles discussed placental problems, malformations and uterine pathologies, abdominal malformations, head, and neck diseases, in addition to 3D prototyping. Still, 4.16% of the studies studied non-obstetric indications for maternal MRI, hydatidiform mole, fetal skeletal structure, in addition to alterations in the development of the fetal spine and spinal cord (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, T2 signal signs are important in placental MRI. The normal placental uterine interface has three layers: the medial T2 low-signal decidua layer, intermediate T2 medium-signal muscle layer, and lateral T2 low-signal serosal layer ( Novis et al, 2021 ). A clear T2 low-signal serous layer can be seen on the surface of the normal bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Placental MRI examinations should be performed in a 1.5-T or 3.0-T scanner. The patient should be in the supine position with a moderately full bladder, which optimizes visualization, especially in cases of suspected placenta percreta ( 13 ) . The basic MRI sequences that provide images rapidly are gradient-echo and spin-echo sequences, such as single-shot fast spin-echo sequences, true fast imaging with steady-state precession (TrueFISP) sequences, and fast imaging employing steady-state acquisition sequences, all of which reduce maternal and fetal motion artifacts.…”
Section: Protocol For Placental Mrimentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) is a relatively new technique to assess placenta accreta spectrum disorders, being used as an ancillary tool to assess placental invasion, and can be useful to define the interface between the placenta and the myometrium ( 14 ) . The total scan time for the examination is 25-35 min, and a radiologist should be present during the examination to guide the technician in case an additional plane perpendicular to the myometrium-placenta interface or the myometrium-bladder interface is needed in order to determine the exact site of the placenta accreta spectrum disorder ( 9 , 13 ) . The use of gadolinium contrast medium should be avoided, because it has been associated with an increased risk of rheumatologic diseases, inflammatory diseases, and infiltrative skin conditions in children with a history of intrauterine exposure to contrast, as well as with an increased incidence of stillbirth and neonatal death ( 13 ) .…”
Section: Protocol For Placental Mrimentioning
confidence: 99%
See 1 more Smart Citation